2000
DOI: 10.1097/00005176-200007000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Pancreatic Enzymes After Stimulation With Secretin Versus Secretin Plus Cholecystokinin

Abstract: Higher pancreatic enzyme levels were obtained after administration of secretin plus cholecystokinin, although the trend did not reach statistical significance. Pancreatic enzyme levels are highest at 5 and 10 minutes, indicating that collections of duodenal fluid should be completed within 10 minutes of the administration of the secretagogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The reason for the difference is not clear, and further clin− ical studies are needed to confirm the apparent usefulness of this protocol. Using direct (endoscopic) measurement of pancreatic enzymes (the "gold standard" for assessing exocrine function), Del Rosario and colleagues demonstrated that secretin was es− sentially as effective statistically as secretin plus cholecystokinin in provoking enzyme release [40]. Thus, although not commonly used as a marker of exocrine function, plasma amylase may be a convenient surrogate for more invasive testing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the difference is not clear, and further clin− ical studies are needed to confirm the apparent usefulness of this protocol. Using direct (endoscopic) measurement of pancreatic enzymes (the "gold standard" for assessing exocrine function), Del Rosario and colleagues demonstrated that secretin was es− sentially as effective statistically as secretin plus cholecystokinin in provoking enzyme release [40]. Thus, although not commonly used as a marker of exocrine function, plasma amylase may be a convenient surrogate for more invasive testing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pancreatic enzyme secretion is stimulated by the cholinergic system and by cholecystokinin (Adler et al 1991;Del Rosario et al 2000). Treatment of the rats with carbamyl ␤-methylcholine, an analog of acetylcholine, led to decreases in levels of Cpn60 that coincided with decreases in pancreatic enzymes (Bendayan et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Hopson et al 10.3389/fped.2022.908542 (129). Interpretation of the test results should be based on the sample with the highest (peak) enzyme activities (129,130).…”
Section: Methods Of Fluid Collection and Analysismentioning
confidence: 99%
“…There is a known dilutional effect of enzyme activities by ductal cell secretions if the fluid is collected beyond 10 min ( 129 ). Interpretation of the test results should be based on the sample with the highest (peak) enzyme activities ( 129 , 130 ).…”
Section: Direct (Stimulatory) Exocrine Function Testsmentioning
confidence: 99%